PERTANGGUNGJAWABAN TERHADAP KESALAHAN ATAU KELALAIAN KURATOR DALAM PENGURUSAN DAN PEMBERESAN HARTA PAILIT (PERSPEKTIF PRIBADI DAN PROFESI) - Rachmah Fidiastuti (2023)
The duties and responsibilities of the curator are very large in carrying out the management and settlement of bankruptcy assets, the implementation of which is still found to be errors or omissions committed by the curator resulting in the responsibility of the curator both as a profession and as a person, so that a study of the responsibility and protection of the curator is urgently needed. The research method used in analyzing the problems under study is normative juridical with a statutory approach and a case approach. Based on the results of the research, it shows that accountability to curators consists of professional and personal responsibilities. Professional responsibility arises when the actions taken by the Curator have harmed the bankruptcy estate due to their negligence, so that the responsibility is borne by the bankruptcy estate. The curator's personal responsibility is attached to the curator who made a mistake on purpose and negligence caused a loss to the bankruptcy estate so that the responsibility is not borne by the bankrupt estate but on the curator personally. Legal protection in carrying out the management and settlement of bankrupt assets is not regulated in the KPKPU Law. Preventively, protection is provided by an organization specifically a professional code of ethics by the Association of Indonesian Receivers and Administrators (AKPI) and is contained in Article 50 of the Criminal Code which is generally accepted, there is no lex specialis regulation. Repressive legal protection is only protection from organizations whose further details are based on association decisions.